Elastyczność rynków pracy a bezrobocie w krajach Unii Europejskiej w okresie kryzysu - Siek, Elżbieta (Gospodarka w Praktyce i Teorii, 2012)
The goal of this paper is to compare the European Union member states regarding the flexibility of their labour markets and an essay to explain the meaning of the level of this flexibility in formation of changes that the labour market undergoes. In the article an analysis and evaluation of the flexibility level of the labour markets in the EU member states, utilising the indexes of the Employment Protection Legislation (EPL), sub-indexes of the economic freedom that concern the employees rights (labour freedom) and indexes of fiscal charge. Subsequently the shaping of the GDP growth speed, unemployment rate and work efficiency in 2008-2011 (quarterly) was presented. Also the evaluation of the mutual relations between these variables was made. An article ends with proper conclusions.